JUAL BELI ONLINE DALAM PERSPEKTIF HUKUM ISLAM (JURNAL HUKUM SEHASEN, 2019)
The use of internet media to support the process of buying and selling very efficient. For the merchants (sellers or online stores), they do not have to bother building a store, tied up with working hours, have a lot of employees, or display physical merchandise. As for the buyer (buyer) the benefits of shopping through online media (internet), among others, can visit merchants anytime and can be done anywhere. In Islamic law there is no prohibition in terms of media used to conduct transactions, but that must be considered by the merchant and the buyer at the time of buying and selling transaction is to consider elements of Sighat al "aqd (Ijab qabul), Mahallul" aqd (object agreement), Al "aqidaian (the parties that execute the agreement). In addition must meet the principles of syari "ah that is buying and selling must be free from element ribawi, gharar and maisyir. Keywords: Sale and Purchase, Online, Islamic Law